"Race", Language and Xenophobia in Joseph Conrad's "Amy Foster". Issue 3 (3rd July 2021) - Sewlall, Harry
Summary: Chinua Achebe's animus against the creator of Heart of Darkness did not simply end with the charge of racism but extended to anti-Semitism and xenophobia as well. The term "xenophobia", which is imbricated in the dialectics of race and language, features strongly in the current politics of diaspora and identity. Conventional scholarship on Conrad's short fiction "Amy Foster" has followed two predominant strands, namely, the extreme loneliness of Yanko Goorall, the central protagonist of this seemingly mis-titled story, and his inability to communicate in a foreign land. This article, from the hermeneutic space afforded by postcoloniality, postulates the construct of "race", as understood in the nineteenth century, as a major catalyst in the breakdown in the marriage of Yanko and Amy. It holds to the view that the tragedy of the former is not so much the outcome of a lack of communication between a castaway and his local English wife, but is predetermined in the face of an ethnocentric, if not rampantly "racist" insular, parochial community. The article concludes that the story is Conrad's study of the racist recesses of the human psyche which manifest in discrimination against the other. Displaced geographically, culturally and linguistically, Yanko (like Conrad himself) is a metonymic inscription of alterity, whose attempts to reclaim his linguistic and cultural identity end in tragedy.